(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Measles is an acute infectious disease caused by the measles virus, a member of the Paramyxoviridae family. Since its identification in the late 1950s, measles has been one of the most widespread infectious diseases, however, extensive vaccination programs have significantly reduced the number of measles cases [2;5;9;11]. Nonetheless, in recent decades, some countries, including Uzbekistan, have seen a slight increase in incidence, underscoring the relevance of this topic.